The Dynamics of Local Representation in Regional Tax Units - Danny Wibowo; Amizawati Mohd Amir (AKRUAL: JURNAL AKUNTANSI, 2026)
Introduction/Main Objectives: This study aims to analyze the role of geographical-cultural representation of tax officials in shaping institutional trust, service legitimacy, and tax compliance in the archipelago. Methods: Using a qualitative approach with a case study method in the Tanimbar Islands, this study examines how the DJP's rotation policy structure and merit system affect the representation of local officials in strategic positions and its implications for public service interactions. Finding / Results: The results of the analysis show that the socio-cultural competence of local employees plays an important role in building social closeness, facilitating communication, and increasing public acceptance of taxation policies. However, the centralized merit system does not fully recognize the strategic value of this social capital, so that local representation is still limited and the adaptation of central policies to the regional context is less than optimal. Conclusion: This study emphasizes that local representation is a key element for the effectiveness of taxation services in the archipelago and requires greater attention in the formulation of human resource and public service policies.